ANALISIS TEOLOGIS PENGGUNAAN PAKAIAN BAGI KAUM WANITA DI DALAM GEREJA BERDASARKAN 1 TIMOTIUS 2:9-10 - Yosep Surahman Situmeang; Gerry C. J. Takaria (Jurnal Koinonia, 2018)
In this study the author tries to examine the use of clothing which is suitablefor use by women in the Church based on the principle in 1 Timothy 2: 9-10. Simplyput, this study is based on four indicators of discussion, namely: Definition ofdressing with modesty 1 Timothy 2:9; The notion of dressing with shamefacednessaccording to 1 Timothy 2:9; The notion of dressing up by not braiding hair by 1Timothy 2:9; and the meaning of costly attire in the context of 1 Timothy 2:9. Thenotion of dressing up appropriately on the basis of 1 Timothy 2: 9 has the meaningthat women will wear clothing that does not invite sexual desire to those who look atit, and will also wear conservative attire. The notion of dressing up modestlyaccording to 1 Timothy 2: 9 is that women will dress themselves respectfully, thuswill not wear impolite clothing one of them is a narrow garment that will show bodyparts. The notion of dressing with no braids based on 1 Timothy 2: 9 is that womenwill not be busy spending time just to decorate their hair, and will not show anystriking hairstyles. The notion of the meaning of costly attire in the context of 1Timothy 2: 9 is a garment bought with a personal motive to boast.